The safe operation of overhead cranes - Skills education Australia; Safetycare Australia Pty. Ltd. ([Australia] : Safetycare Australia)
The video program has been designed to clearly identify all the steps necessary to enable efficient and safe operation of any overhead crane
Title from title screen
Keywords: Cranes, derricks, etc. -- Law and legislation; Cranes, derricks, etc. -- Electric equipment